2015
DOI: 10.1089/jamp.2015.1224
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Disease Severity in Asthma and Chronic Obstructive Pulmonary Disease on Inhaler-Specific Inhalation Profiles Through the ELLIPTA® Dry Powder Inhaler

Abstract: Background: Two studies were undertaken to characterize the maximal effort inhalation profiles of healthy subjects and patients with asthma or chronic obstructive pulmonary disease (COPD) through a moderate-resistance dry powder inhaler (DPI). Correlations between inhaler-specific inhalation characteristics and inhaler-independent lung function parameters were investigated.Methods: Healthy subjects (n = 15), patients with mild, moderate, or severe asthma (n = 45), and patients with mild, moderate, severe, or v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 22 publications
3
43
0
4
Order By: Relevance
“…In an in vitro study that replicated inhaler-specific patient inhalation profiles that were previously recorded in vivo using the Electronic Lung (eLung TM ), drug dose delivery via the Ellipta Ò DPI was consistent across the range of patient representative inhalation parameters for all therapies such as formoterol/ vilanterol, umeclidinium/vilanterol, and formoterol [49]. A recent study showed that patients with mild to very severe COPD could also generate sufficient inspiratory flows for optimum drug delivery via Ellipta Ò [50]; it should be noted that this may not always be true in real life.…”
Section: Ellipta òmentioning
confidence: 57%
“…In an in vitro study that replicated inhaler-specific patient inhalation profiles that were previously recorded in vivo using the Electronic Lung (eLung TM ), drug dose delivery via the Ellipta Ò DPI was consistent across the range of patient representative inhalation parameters for all therapies such as formoterol/ vilanterol, umeclidinium/vilanterol, and formoterol [49]. A recent study showed that patients with mild to very severe COPD could also generate sufficient inspiratory flows for optimum drug delivery via Ellipta Ò [50]; it should be noted that this may not always be true in real life.…”
Section: Ellipta òmentioning
confidence: 57%
“…Some in vitro studies indicate that the fine-particle dose from DPIs is reduced when inspiratory flow is Ͻ 60 L/min, [141][142][143][144] whereas other studies show little effect of flow. 145,146 Diskus lung delivery may be suboptimal with a peak inspiratory flow Ͻ 60 L/min.…”
Section: Inhalation Device Selectionmentioning
confidence: 99%
“…9 In a study conducted in an out-patient research setting, using an instrumented Ellipta inhaler, severe to very severe subjects with COPD had shorter inspiratory times and tended to have impaired inspiratory flow (Ͻ 60 L/min). 144 Decreased inspiratory flow has been observed when patients with COPD are clinically stable 36,140,143,147 and during exacerbations requiring hospitalization. 125,126,128 One study in subjects with COPD recently discharged from the hospital were instructed in the use of a Diskus inhaler with the INCA smart inhaler device.…”
Section: Inhalation Device Selectionmentioning
confidence: 99%
“…The inspiratory flow rate is an important inhalation profile parameter because of its direct influence on the dose delivery from most DPIs. The Ellipta device produces consistent dose delivery at flow rates over 30L/min [13,15] and this covers the inhalation rates across asthma and COPD disease severity, with even patients who suffer from very severe COPD able to generate an inspiratory effort of 41.6L/min whilst using the inhaler [15,16]. The particle size and fine particle fraction of the Ellipta inhalers vary by the medication delivered.…”
Section: Design Featuresmentioning
confidence: 99%